RETORIKA STORYTELLING HOROR DALAM VIDEO “BAYANGAN PULANG” CHANNEL YOUTUBE NADIA OMARA - Rara Ayu Nareswari, Kirana; Muhajir; Naka Andrian, Setia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the transformation of horror stories from conventional forms to participatory multimedia narrative experiences on YouTube, using a case study of the video titled "Shayangan Pulang" by Nadia Omara. The main focus is to identify the application of rhetorical elements, Storytelling techniques, and YouTube's role in supporting digital narratives. Using a qualitative case study approach, data was obtained through content analysis of verbal, visual, and audio elements, as well as audience reception in the comments section. The analysis was conducted using Aristotle's rhetorical framework (ethos, pathos, and logos) as well as the theories of digital Storytelling and media convergence. The research findings indicate that pathos is the most dominant element, manifested through gripping sound effects, vocal modulation, dramatic pauses, and a non-linear structure to evoke fear. Ethos & Logos credibility is built through a consistent narrator persona (ethos), while the logic of the storyline is maintained despite the supernatural theme (logos). The Role of YouTube: Interactivity features and participatory culture significantly strengthen the audience's emotional and social engagement. This research demonstrates that integrating classical rhetoric with digital techniques can create an immersive horror experience and enhance audience engagement in digital media.